A trajectory planner for manipulators using genetic algorithms - Pires, E. J. Solteiro (1999)
This paper proposes a genetic algorithm (GA) to generate trajectories for robotic manipulators. The objective is to minimize the ripple in the time evolution of robot positions and velocities. Moreover, the manipulator is required to reach a predefined goal without colliding with obstacles in the workspace. The article presents the results for several redundant and non-redundant robot manipulators.